Selective Shrub Management to Preserve Mediterranean Forests and Reduce the Risk of Fire: The Case of Mainland Portugal - Raposo, Mauro (2020)
The recurrent rural fires that occur annually in Portugal have reached great proportions due to a lack of effective landscape management. Attempts to solve this problem led to the legal imposition to cut back the vegetation in the fuel management areas, which has had a negative effect on biodiversity. National legislation protects three native plant species (Quercus suber, Q. rotundifolia and Ilex aquifolium). European legislation, through the Habitats Directive, also identifies some plant species that require strict protection, although it leaves out several endemic and rare plants. In this work we aim to differentiate the types of shrub plant material and their pyrophilic behavior, since the physical and chemical characteristics of vegetation can enhance or inhibit the progression of fire. Thus, based on phytosociological science, specifically at the class level, the dynamics of potential climatophilous vegetation in Portugal are presented and the classes that should be prioritized for control are identified. Based on ecology, it was possible to identify morphological patterns of vegetation. In short, the genera targeted for control under the National Forest Fire Protection Plan belong to the furthest states from the mature potential of a forest, generally consisting of heliophile shrubs and typically growing in degraded soils. The shrub species to be valued belong to dynamic states closer to the mature potential, consisting mainly of broad-leaved shrubs and those growing in better-preserved soils.